1974
DOI: 10.4319/lo.1974.19.3.0429
|View full text |Cite
|
Sign up to set email alerts
|

Production of pelagic Sargassum and a blue‐green epiphyte in the western Sargasso Sea1

Abstract: North of 30"N Sargassum production averaged about twice that to the south, possibly related to the degree of winter mixing.Production rates were relatively high in continental shelf areas or near land masses but showed no major seasonal variations nor was there an obvious relationship with concentrations of NO,, NOa, NH:,, and POA. Under normal daylight conditions in October Sargassum photosynthesizes at a maximum rate. Average carbon turnover time is no more than 40 days and Sargassum and its epiphytes contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 9 publications
0
26
0
Order By: Relevance
“…According to Carpenter & Cox (1974), the distribution pattern of the Sargassum epiphytes can be directly correlated with differences in concentration of nutrients in the Sargasso Sea. Menzel et al (1963) and Menzel & Ryther (1960) have shown that low iron content limits the production of phytoplankton in the southern Sargasso Sea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Carpenter & Cox (1974), the distribution pattern of the Sargassum epiphytes can be directly correlated with differences in concentration of nutrients in the Sargasso Sea. Menzel et al (1963) and Menzel & Ryther (1960) have shown that low iron content limits the production of phytoplankton in the southern Sargasso Sea.…”
Section: Discussionmentioning
confidence: 99%
“…Menzel et al (1963) and Menzel & Ryther (1960) have shown that low iron content limits the production of phytoplankton in the southern Sargasso Sea. The distribution pattern of the nitrogen-fixing Dichotrix, which occurs as an epiphyte on Sargassum, is linked with the available iron in this region (Carpenter & Cox, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…Growth experiments suggest little effect of temperature on Sargassum growth above 18°C (Carpenter & Cox 1974), with reduced growth below this temperature for both species (Hanisak & Samuel 1987). S. fluitans may experience low-temperature stress starting at 24°C (Hanisak & Samuel 1987), however observations of Sargassum below 18°C showed signs of distress and wilting (Winge 1923).…”
Section: Sargassum Model Descriptionmentioning
confidence: 99%
“…Thus, Sargassum may not act as an entirely passive tracer, since its distribution can be influenced by growth and mortality in addition to advection. Sargassum primary production varies across its range (Carpenter & Cox 1974), and is generally higher in neritic waters with higher nutrient availability (Lapointe 1995). Pelagic Sargassum underpins a diverse ecosystem (Butler et al 1983, Laffoley et al 2011, Huffard et al 2014) supporting a wide range of fish species (Hoffmayer et al 2005) and playing a role in the migration of juvenile sea turtles (Carr & Meylan 1980, Witherington et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…The standing crop of Dichothrix fucicola in the North Atlantic varies from about 1.5 mg g -1 Sargassum in the SW Sargasso Sea to about 70 mg g -1 Sargassum on the U.S. shelf off New Jersey and Delaware. These cyanobacteria may contribute substantially to primary production of the floating macroalgae (Carpenter & Cox 1974). Furthermore, as the dominant epiphyte on floating S. natans , Dichothrix fucicola contributes significantly to the overall epiphyte respiration of the Sargassum community (Smith et al 1973).…”
Section: Cyanobacteriamentioning
confidence: 99%